Hearing Dysfunction in a Large Family Affected by Dominant Optic Atrophy (OPA8-Related DOA): A Human Model of Hidden Auditory Neuropathy - Santarelli, Rosamaria; La Morgia, Chiara; Valentino, Maria Lucia; Barboni, Piero; Monteleone, Anna; Scimemi, Pietro; Carelli, Valerio (Frontiers in Neuroscience, 2019)
Hidden auditory neuropathy is characterized by reduced performances in challenging auditory tasks with preservation of hearing thresholds, resulting from diffuse loss of cochlear inner hair cell (IHC) synapses following primary degeneration of unmyelinated terminals of auditory fibers. We report the audiological and electrophysiological findings collected from 10 members (4 males, 6 females) of a large Italian family affected by dominant optic atrophy associated with the OPA8 locus who complained of difficulties in understanding speech in the presence of noise. The patients were pooled into two groups, one consisting of 4 young adults (19-50 years) with normal hearing, and the other made up of 6 patients of an older age (55-72 years) showing mild hearing loss. Speech perception scores were normal in the first group and decreased in the second. Otoacoustic emissions (OAEs) and cochlear microphonics (CMs) recordings were consistent with preservation of outer hair cell (OHC) function in all patients, whereas auditory brainstem responses (ABRs) showed attenuated amplitudes in the first group and severe abnormalities in the second. Middle ear acoustic reflexes had delayed peak latencies in all patients in comparison with normally-hearing individuals. Transtympanic electrocochleography (ECochG) recordings in response to 0.1 ms clicks at intensities from 120 to 60 dB SPL showed a reduction in amplitude of both summating potential (SP) and compound action potential (CAP) together with delayed CAP peak latencies and prolonged CAP duration in all patients in comparison with a control group of 20 normally-hearing individuals. These findings indicate that underlying the hearing impairment in OPA8 patients is hidden AN resulting from diffuse loss of IHCs synapses. At an early stage the functional alterations only consist of abnormalities of ABR and ECochG potentials with increased latencies of acoustic reflexes, whereas reduction in speech perception scores become apparent with progression of the disease. Central mechanisms increasing the cortical gain are likely to compensate for the reduction of cochlear input.